Does the South African government have a duty to fund influenza vaccination of adults 65 years and older? - Sarangarajan, Ruach; Ewuoso, Cornelius (Frontiers in Public Health, 2024)
In this paper, we draw on the thinking about solidarity, reciprocity and distributive justice grounded in Afro-communitarian ethics from the Global South to argue for institutions, particularly the South African (SA) government, have a prima facie duty to foster influenza vaccine uptake for adults 65 years and older. Although we focus specifically on the South African government to defend our position, we believe that our argument extends to all governments. Notably, these duties are that the SA government ought to make influenza vaccines freely available for the elderly in both the public and private health facilities, provided financial allocation and their extant relationships allow for this. Further, the SA government has a duty to improve influenza vaccine procurement and availability in the country, preferably through increasing manufacturing capabilities. This paper is intrinsically valuable to promote epistemic justice, thereby contributing towards the decolonization of the global healthcare system. Moreover, this project has social significance in contributing to mitigation efforts against future public health challenges associated with population ageing in resource-limited developing African nations, wherein the impact of population transition will be felt most.